Old Overnight: Experiences of Age-Based Recommendations in Response to the COVID-19 Pandemic in Sweden. Issue 4 (3rd September 2021) - Nilsson, Gabriella; Ekstam, Lisa; Axmon, Anna; Andersson, Janicke
ABSTRACT: The Swedish response to the COVID-19 pandemic included age-based recommendations of voluntary quarantine specifically for those 70 years of age or older. This paper investigates the experiences of a sudden change of policy in the form of an age restriction that trumped the contemporary active aging ideal. A web-based qualitative survey was conducted in April 2020. Through manual coding of a total of 851 responses, six different ways of relating to the age-based recommendations were identified. The results show that age is not an unproblematic governing principle. Instead, in addition to protecting a vulnerable group, the age-based recommendation meant deprivation of previously assigned individual responsibility and, consequently, autonomy. It is shown how respondents handled this tension through varying degrees of compliance and resistance. Findings highlight the importance of continuously tracking the long-term consequences of age-based policy to avoid negative self-image and poorer health among older adults.